2004
DOI: 10.1111/j.1365-2036.2004.02248.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: the efficacy, adverse events, and adherence related to first‐line anti‐Helicobacter pylori quadruple therapies

Abstract: SUMMARYBackground: Owing to rising drug-resistant Helicobacter pylori infections, currently recommended proton-pump inhibitor-based triple therapies are losing their efficacy, and regimens efficacious in the presence of drug resistance are needed. Aims: To summarize the efficacy, safety and adherence of first-line quadruple H. pylori therapies in adults. Methods: Meta-regression models identified factors explaining variation in the efficacy of first-line quadruple therapies from 145 treatment arms. Estimates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(173 citation statements)
references
References 82 publications
10
147
0
5
Order By: Relevance
“…We couldn't detect a statistically significant difference between the regimen types (triple or quadruple regimens) with respect to the gastrointestinal side-effects. In one meta-analysis which was done in 2004, it was found that the occurrence of adverse events was consistently similar for the triple or quadruple regimens in the 10 controlled trials [20].…”
Section: Discussionmentioning
confidence: 99%
“…We couldn't detect a statistically significant difference between the regimen types (triple or quadruple regimens) with respect to the gastrointestinal side-effects. In one meta-analysis which was done in 2004, it was found that the occurrence of adverse events was consistently similar for the triple or quadruple regimens in the 10 controlled trials [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recommended treatment duration varies according to individual guidelines; for instance, a treatment duration of more than 1 wk is recommended in Europe, while 1-2 wk and 1 wk are recommended in the United States and South Korea, respectively [8,15,16] . One report indicated that in some metronidazole-resistant areas, extending the bismuth-based quadruple therapy treatment duration to 10-14 d was highly effective [17] ; similarly, another study found that administering metronidazole for 14 d could overcome the negative influence of metronidazole resistance [18] . There is also much debate about the value and efficacy of 7-vs 14-d of bismuth-based quadruple therapy as a second-line eradication therapy in South Korea [14,19,20] .…”
Section: Introductionmentioning
confidence: 99%
“…Adverse events were reported in up to 50% of patients receiving triple therapy. 30 Most of the adverse events were mild, and did not lead to the discontinuation of therapy. In particular, antibiotic administration is often associated with gastrointestinal side effects, such as diarrhea, nausea, vomiting, bloating, and abdominal pain.…”
Section: Discussionmentioning
confidence: 99%